The Assessment Performance Indicator of Integrating the SDGs for Extraction Companies - Herlyana, Alifia; Boyska, Raymond; Utha, Maria Ariesta (SAFE-Network, 2025)
Indonesia possesses vast natural resources and has established a robust mining sector that includes both mineral and coal industries. Mining plays a vital role in economic development but also poses significant sustainability challenges, particularly in balancing environmental, social, and economic dimensions. This study aims to develop a metric integrated aspect parameter sustainability assessment model by evaluating two major mining companies in Indonesia that have consistently published sustainability reports for over ten years and were awarded gold ratings in the 2024 PROPER assessment. This study adopts a mixed-methods approach that integrates qualitative issue mapping with quantitative analysis, focusing on three mining companies in Indonesia that achieved a Gold PROPER rating in 2024, namely PT AAA and PT BBB. The sampling method used was purposive sampling. Data analysis employed a composite index approach, integrating the Responsible Mining Index (RMI) and the Dow Jones Sustainability Index (DJSI). Out of 416 mapped indicators, the strongest alignment was observed with SDG 8 (Decent Work and Economic Growth), SDG 12 (Responsible Consumption and Production), SDG 13 (Climate Action), and SDG 16 (Peace, Justice, and Strong Institutions). In contrast, SDG 4 (Quality Education), SDG 7 (Affordable and Clean Energy), and SDG 17 (Partnerships for the Goals) were underrepresented.